2015
DOI: 10.1055/s-0035-1557320
|View full text |Cite
|
Sign up to set email alerts
|

Biofeedback and cognitive behavioral therapy for Egyptian adolescents suffering from chronic fatigue syndrome

Abstract: We aimed to evaluate the efficacy of cognitive behavioral therapy (CBT) aided by biofeedback in rehabilitating Egyptian adolescents who were suffering from chronic fatigue syndrome (CFS). Out of 298 screened individuals with chronic fatigue, only 159 adolescents were eligible for study; of them 63 cases lost follow up and four cases were further excluded because of switch leaving only 92 cases with complete database. Age range of enrolled cases was 10?14 years and male/female ratio (1/2.5). They were recruited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…Compared with the ‘inactive’ class, being in the ‘light’ or ‘active’ class was associated with improved physical function by 10.4 and 15.3 points, respectively, which is greater than the minimal clinically importance difference for the SF36-PFS 23 42 43. There was some evidence to suggest that being in the ‘light’ class was associated with lower levels of fatigue compared with being in the ‘inactive’ class, but adjusting for time since diagnosis attenuated this association.…”
Section: Discussionmentioning
confidence: 90%
“…Compared with the ‘inactive’ class, being in the ‘light’ or ‘active’ class was associated with improved physical function by 10.4 and 15.3 points, respectively, which is greater than the minimal clinically importance difference for the SF36-PFS 23 42 43. There was some evidence to suggest that being in the ‘light’ class was associated with lower levels of fatigue compared with being in the ‘inactive’ class, but adjusting for time since diagnosis attenuated this association.…”
Section: Discussionmentioning
confidence: 90%
“…In total, we identified 26 RCTs or observational studies that investigated treatment interventions in paediatric CFS/ME. However, 19 of these studies did not measure pain at any time point,24–43 and two studies measured pain at a single time point only 10 44. They were therefore excluded from this review.…”
Section: Resultsmentioning
confidence: 99%
“…They were therefore excluded from this review. Four of the studies included the prevalence of self-reported symptoms, for example, muscle aches, abdominal discomfort and tender lymph nodes, but did not include measures of pain severity 24 25 31 41. The remaining studies did not discuss pain at all.…”
Section: Resultsmentioning
confidence: 99%
“…The final RCT from Al-Haggar et al 4 (n=159) compared CBT plus biofeedback with usual care where children were offered symptomatic treatment only. Participants in the CBT arm received 40–60 sessions over 18 months.…”
Section: Commentarymentioning
confidence: 99%